Inverse association of oxidative balance score with depression and specific depressive symptoms among cancer population: Insights from the NHANES (2005–2020) - Hanli Bu; Mingzhen Lv; Linxian Wang; Dan Jiang; Yi Ding; Zheya Wang; Yaoyao Hu; Qin Zhuang; Zhenzhen Tian (PLoS ONE, 2025)
Background The rising prevalence of depression among cancer patients is alarming. This study examines the relationship between the Oxidative Balance Score (OBS)—a composite measure of dietary and lifestyle factors—and depression, including specific depressive symptoms in this population. Methods Data were analyzed from 3,280 adult cancer patients collected in NHANES from 2005–2020. Depression was assessed using the Patient Health Questionnaire-9 (PHQ-9), where a score of 10 or above indicated depression. Symptoms experienced frequently were classified as specific depressive symptoms. Weighted logistic regression models were utilized to explore the correlation between OBS and depression, along with distinctive depressive symptoms. Results There was a negative correlation between OBS and depression. The highest quartile of OBS (OR 0.313, 95% CI: 0.161–0.609), along with dietary OBS (OR 0.429, 95% CI: 0.234–0.786) and the third quartile of lifestyle OBS (OR 0.404, 95% CI: 0.226–0.722), was associated with reduced depression risk. OBS was correlated with lower risks of all four somatic depressive symptoms and one cognitive symptom. Dietary OBS was associated with fewer risks of three somatic symptoms and one cognitive symptom. Lifestyle OBS showed a negative correlation with two somatic symptoms. Stratified analyses indicated that the inverse relationship between OBS and depression risk was consistent across subgroups, including females and individuals under 65. a nonlinear association was observed between OBS (p = 0.024), dietary OBS (p<0.001), lifestyle OBS (p = 0.021), and depression. Conclusions OBS is inversely related to depression and specific depressive symptoms in cancer patients. Encouraging a diet and lifestyle rich in antioxidants may help reduce the risk of depression in this group.